Pengabdian Kepada Masyarakat Mengenai Peningkatan Pengetahuan Pasangan Usia Subur Tentang Penggunaan Kontrasepsi Jangka Panjang di Desa Batujajar - Anne Loisza; Intan Karlina; Azka Meylita; Nur Aliya Sifa; Salsabila Konita Putri; Dwi Takhsya Ma’ashilhaq; Fadhia Siti Azizah Nuraeni; Hany Hany; Riva Nazia Salsyabila; Salsa Sabila Azzahra; Asti Aida Putri; Chinta Salma Az-Zahra; D. Alni Febrianingsih (PELITA NUSA TENGGARA, 2026)
Problem with couples of childbearing age (PUS) in Batujaja Barat Village is not merely a matter of participation rates, but rather the inappropriate choice of methods and misperceptions among couples of childbearing age (PUS). Many PUS in the limiting category want to stop having children but continue to use short-term contraception or do not use any contraception at all due to concerns about side effects. The types of long-acting reversible contraception (LARC) introduced in this activity included intrauterine devices (IUDs) and implants. The aim of this community service was to increase PUS knowledge about the safety and advantages of LARC in order to improve the accuracy of its use. The methods used were interactive health education through lectures, two-way discussions, and the use of leaflets. This activity involved 29 PUS at the Kenari 02 Posyandu with a pretest-posttest evaluation design. The evaluation results showed a significant shift in knowledge levels. The evaluation results showed an increase in knowledge levels after the intervention. Before the education, some participants were in the low knowledge category, while after the education there was an increase in the proportion of participants with good knowledge. Statistical analysis using the Wilcoxon Signed Rank Test showed a significant difference in knowledge levels before and after the intervention (p < 0.05). Before the intervention, there were 10 participants in the low knowledge category (34.48%). After the intervention, the number of respondents with low knowledge decreased to 5 (17.24%). In the adequate knowledge category, the number remained the same, from 9 people (31.03%) in the pretest to 9 people (31.03%) in the post-test. Meanwhile, respondents with good knowledge increased from 10 people (34.48%) before the intervention to 15 people (51.72%) after the intervention. This change proves that the material presented was well absorbed by the participants. Interactive discussions successfully corrected participants' misconceptions and increased their confidence in choosing the right contraceptive method. The conclusion of this activity is that health education effectively improves contraceptive literacy among partners and encourages more stable and safer contraceptive use behaviour.